Реєстрація зразків-стандартів алелів локусів високомолекулярних субодиниць глютенінів Aegilops biuncialis Vis. - Козуб, Н.О.; Созінов, І.О.; Бідник, Г.Я.; Дем'янова, Н.О.; Созінов, О.О. (Фактори експериментальної еволюції організмів, 2013)
Aims. The objective of the investigation was selection and registration of Aegilops biuncialis Vis. accessions that may serve as standards for high-molecular weight glutenin subunit alleles. Methods. Ae. biuncialis accessions derived from Crimean populations were propagated on the experimental plot. SDS electrophoresis of high-molecular weight glutenin subunits was used to identify alleles at the Glu-U1 and Glu-Mb1 loci. Results. The most frequent alleles among the collection of propagated accessions of Ae. biuncialis were Glu-U1b and Glu-Mb1a. Fifteen accessions were registered at the National Centre of Plant Genetic Resources of Ukraine. The set of registered accessions includes six different alleles at the Glu-U1 locus and seven alleles at Glu-Mb1. Conclusions. Fifteen accessions of Ae. biuncialis registered in the National catalogue of NCPGRU may serve as standards for six alleles at the Glu-U1 locus and seven alleles at Glu-Mb1.